Pengaruh Kombinasi Komposisi Media Organik dan Konsentrasi Nutrisi terhadap Daya Hasil Tanaman Melon (Cucumis melo L.) - Khoirul Bariyyah; Sigit Suparjono; Usmadi Usmadi (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2015)
This research was addressed to study the effect of plant growth media composition and nutrients concentration on yield of Cucumis melo L. The research was designed in complete factorial test of 4x4 with three replicates. Mixed growth media of bokashi:cocopeat:husk charcoal were tested in four compositions, i.e. 90%:5%:5% (M1), 80%:10%:10%(M2), 70%:15%:15% (M3) and 60%:20%:20% (M4) respectively. The other tested factor was nutrients concentraion that consists of four levels, i.e. control/no nutrient given (K0), 2 g/L (K1), 4 g/L (K2) and 6 g/L (K3). The Action 434 variety of Cucumis melo L. seedlings were then transplanted into 10 kg’s polybag and allowed to grow till harvested. The results showed that Chlorophyll content of M1 plants were higher than others, but the highest sugar content was resulted by M3 plants, and the highest thick of flesh fruit was resulted by interaction 60% bokashi:20% cocopeat:20% husk charcoal with 4 g/L nutrient concentration.